Bit Error Rate Analysis Using QAM Modulation for Satellite Communication Link. (2016) - Usha, S.M.; Nataraj, K.R.
Abstract: The two main advances in the twentieth century are automobiles and telecommunication. These two fields changed the way people lived. The telecommunication systems have now made it likely to communicate effectively anyone at any time. Artificial earth satellites have been used in communication system become an essential part of the world's telecommunication structure. Satellite allow people to talk by telephone and exchange electronic mail from anywhere in the world and receive hundreds of TV channels in their homes. The modulation is the technique used for multiline communication. The modulation is nothing but altering the characteristics of the carrier wave with the characteristics of another wave called as modulating signal. In this paper satellite communication link is established using Simulink tool. The Bit Error Rate (BER) analysis is performed using different configuration of QAM (Quadrature Amplitude Modulation) such as 16 QAM, 64 QAM, 128 QAM and 256 QAM with the same satellite link. In the downlink channel the free space path loss of 196 dB and phase and frequency offset are introduced. The transmitter signal and received signal after and before filtering are represented. This paper is implemented by using MATLAB and Simulink. The results are analyzed and compared.